2016
DOI: 10.1016/j.jacl.2016.06.013
|View full text |Cite
|
Sign up to set email alerts
|

Mortality reduction in patients treated with long-term intensive lipid therapy: 25-year follow-up of the Familial Atherosclerosis Treatment Study—Observational Study

Abstract: BACKGROUND Cardiovascular disease (CVD) begins early in life and is associated with both the number of risk factors present and length of exposure to these risk factors including hyperlipidemia. OBJECTIVES The clinical benefit of intensive lipid therapy over 25 years was investigated in the Familial Atherosclerosis Treatment Study – Observational Study (FATS-OS). METHODS Of 175 CAD subjects with mean LDL-C of 191 mg/dl and mean age of 50 years, who completed the randomized and placebo-controlled FATS, 100 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 23 publications
0
2
0
1
Order By: Relevance
“…Further studies have assessed the efficacy of nicotinic acid used together with other available lipid-lowering drugs. The FATS, a double-blind study evaluating the effects of nicotinic acid administered in combination with colestipol (Zhao et al, 2016). The relative efficacy of the method was compared to treatment with lovastatin or conventional treatment (either colestipol in subjects with higher baseline LDL-C or placebo).…”
Section: Clinical Effects Of Niacinmentioning
confidence: 99%
“…Further studies have assessed the efficacy of nicotinic acid used together with other available lipid-lowering drugs. The FATS, a double-blind study evaluating the effects of nicotinic acid administered in combination with colestipol (Zhao et al, 2016). The relative efficacy of the method was compared to treatment with lovastatin or conventional treatment (either colestipol in subjects with higher baseline LDL-C or placebo).…”
Section: Clinical Effects Of Niacinmentioning
confidence: 99%
“…Niacin, a vitamin B, has long been used to increase HDL [ 31 - 33 ]. In the Coronary Drug Project [ 34 ], that enrolled men with a history of MI, it was demonstrated that niacin reduced the rate of recurrent non-fatal MI and decreased 15-year total mortality by 11%.…”
Section: Therapeutic Approaches To Raise Plasma Hdlmentioning
confidence: 99%
“…Somam-se ainda estudos de intervenção, na prevenção primária e secundária, que ao reduzirem os valores de LDL-c, evidenciaram diminuição da mortalidade por doenças cardiovasculares. (Zhao et al, 2016;Cholesterol Treatment Trialists' (CTT) Collaboration, 2015). (Tabas, 2016).…”
Section: Diversos Estudos Populacionais Sendo O Mais Clássico O Estuunclassified